Indirect restorations in composite resin in cavities with different depths: Case report (Research, Society and Development, 2021)
Indirect composite resin restorations are commonly used on posterior teeth in different cavities, allowing greater wear resistance, marginal adaptation, establishment of proximal contacts and greater hardness, since it undergoes the process of thermopolymerization. The aim of this study is to report a clinical case of replacing amalgam restorations by indirect restorations in composite resin in cavities with different depths. Female patient, 34 years old, went to the dental clinic of a private institution, complaining of aesthetic dissatisfaction in amalgam restorations on teeth 45, 46 and 47. After clinical examination, due to the extension of the cavities, it was suggested to perform indirect restorations in composite resin in the three elements. After removing the amalgam, with a diamond tip, the depths of the tooth cavities were evaluated. In tooth 45, an endodontic treatment and installation of a fiberglass pin were performed. In tooth 46, an indirect pulp capping was performed and in tooth 47, no pulp treatment was performed. Subsequently, the teeth were prepared for indirect restorations with diamond tip # 3131, then they were molded with addition silicone, proceeding with casting of the mold, with type IV plaster. The model was die-cut using the double casting technique and the composite resin restorations were made on the model. In the following session, the restorations were cemented with dual self-adhesive resin cement. Finally, occlusal adjustment was performed, followed by finishing and polishing. The therapies employed were effective in recovering the anatomical and aesthetic shape of the dental elements involved.